Peptide therapeutics that directly target transcription factors. Issue 1 (10th February 2018) - Inamoto, Ichiro; Shin, Jumi A.
Abstract: Transcription factors regulate gene expression in cells and control cellular development, function, and death. Dysregulation of transcription factors is often associated with disease, including cancer. As such, transcription factors are attractive targets for design of therapeutics against disease. Transcription factors function using protein‐protein and protein‐DNA interactions that occur over relatively large surface areas: this lack of a small and defined "ligand binding site" has proven to be challenging to target with small molecules. Peptide therapeutics, therefore, provide an alternate approach toward design of inhibitory agents. Transcription factors are conveniently modular by design: just the small domain that is responsible for the transcription factor's DNA binding or a protein‐protein interaction or another function, can serve as the basis for novel peptide therapeutics. In this review, examples of peptides that directly interfere with transcription factors will be discussed. Abstract :